2021
DOI: 10.1099/jmm.0.001372
|View full text |Cite
|
Sign up to set email alerts
|

Acceptable performance of the Abbott ID NOW among symptomatic individuals with confirmed COVID-19

Abstract: Introduction. The ID NOW is FDA approved for the detection of SARS-CoV-2 in symptomatic individuals within the first 7 days of symptom onset for COVID-19 if tested within 1 h of specimen collection. Gap statement. Clinical data on the performance of the ID NOW are limited, with many studies varying in their study design and/or having small sample size. Aim. In this study we aimed to determine the clinical performance of the ID NOW compared to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…While ID NOW testing was mandated to be done within 1 hour from collection, short periods of time from transportation may potentially affect performance. 10 Secondly, a higher proportion of individuals with lower viral loads may be tested in hospitals and via mobile. For mobile testing (mostly outbreaks), individuals with symptoms were possibly early in their symptom onset at time of testing, whereas those presenting to hospitals were possibly late in their symptom onset; both of which can be associated with higher Ct values and, therefore, lower viral loads.…”
Section: Discussionmentioning
confidence: 99%
“…While ID NOW testing was mandated to be done within 1 hour from collection, short periods of time from transportation may potentially affect performance. 10 Secondly, a higher proportion of individuals with lower viral loads may be tested in hospitals and via mobile. For mobile testing (mostly outbreaks), individuals with symptoms were possibly early in their symptom onset at time of testing, whereas those presenting to hospitals were possibly late in their symptom onset; both of which can be associated with higher Ct values and, therefore, lower viral loads.…”
Section: Discussionmentioning
confidence: 99%
“…Such ‘false positives’ may arise because of detection of residual viral RNA following recent infection in individuals who are post-infectious (likely explanation in 5/31), or because a single SARS-CoV-2 PCR is an imperfect reference standard and may itself miss individuals with current infection (likely in 9/31) [ 3 ]. Stokes et al found that on further evaluating nine ID NOW false positives, 5/9 were PCR positive on repeat testing of the same sample using different assays [ 15 ]. Our remaining false positives may represent asymptomatic COVID-19 with a false-negative PCR [ 31 , 32 ] or contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Results can be integrated automatically with hospital records which saves time and error by avoiding manual recording, and allows easy evaluation and audit. The reported performance of ID NOW in the literature to date has mostly come from small studies across a range of settings, with sensitivities ranging from 55-98% and specificities 95-100% when using RT-PCR as the gold standard [ 8 , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ]. Sensitivity approaches 100% when PCR results with a cycle threshold (Ct) value >30, suggesting a lower viral load, are excluded [ 15 , [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 This NAAT-RDT is simple and provides rapid results with high sensitivity and specificity, but its single-specimen processing limits its scalability for testing large populations. [14][15][16] Instead, this NAAT-RDT was evaluated for rapid confirmation of SARS-CoV-2 using RTB from positive Ag-RDTs, at the site of sample collection (Table 1). The assessment was performed in two stages on asymptomatic individuals presenting to urban rapid testing sites.…”
Section: Introductionmentioning
confidence: 99%